2014
DOI: 10.5755/j01.eee.20.9.8711
|View full text |Cite
|
Sign up to set email alerts
|

Development of Control System of the Single Phase Multi-input Inverter for Microgrids

Abstract: Scheme of the small-scale microgrid inverter control system is investigated and described. The researched microgrid is intended for small-scale power users, which maximum capacity does not exceed 5 kW. Results of the control system research are presented. Method of mathematical modelling was used for researches of the system. The MATLAB/SIMULINK model was worked out for this purpose. The model was based on the SymPowerSystems library. The main target of the researches was active and reactive power control in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The study found that electrode boilers can reduce greenhouse gas emissions and improve operational reliability. Ramonas Č et al [8] studied a space heating system consisting of a small wind turbine and a boiler and verified that the system is feasible. Yang et al [9] established a multi-objective optimization model of wind farm capacity based on wind power generation and heat supply by electron beam transmission system.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that electrode boilers can reduce greenhouse gas emissions and improve operational reliability. Ramonas Č et al [8] studied a space heating system consisting of a small wind turbine and a boiler and verified that the system is feasible. Yang et al [9] established a multi-objective optimization model of wind farm capacity based on wind power generation and heat supply by electron beam transmission system.…”
Section: Introductionmentioning
confidence: 99%